BLOOD PRESSURE GENETIC RISK SCORE PREDICTS BLOOD PRESSURE RESPONSES TO DIETARY SODIUM AND POTASSIUM: THE GENSALT STUDY - Nierenberg, Jovia (Hypertension, 2017)
We examined the association between genetic risk score (GRS) for blood pressure (BP), based on SNPs identified in previous BP genome-wide association study meta-analyses, and salt- and potassium-sensitivity of BP among participants of the Genetic Epidemiology Network of Salt-Sensitivity (GenSalt) study. The GenSalt study was conducted among 1,906 participants who underwent a 7-day low-sodium (51.3 mmol sodium/day), 7-day high-sodium (307.8 mmol sodium/day), and 7-day high-sodium plus potassium (60 mmol potassium/day) intervention. BP was measured nine times at baseline and at the end of each intervention period using a random-zero sphygmomanometer. Associations between systolic BP (SBP), diastolic BP (DBP) and mean arterial pressure (MAP) GRS and respective SBP, DBP and MAP responses to the dietary interventions were assessed using mixed linear regression models that accounted for familial dependencies and adjusted for age, gender, field center, body mass index and baseline BP. As expected, baseline SBP, DBP, and MAP significantly increased per quartile increase in GRS (P=2.7×10(−8), 9.8×10(−8), and 6.4×10(−6) respectively). In contrast, increasing GRS quartile conferred smaller SBP, DBP, and MAP responses to the low-sodium intervention (P=1.4×10(−3), 0.02, and 0.06, respectively) and smaller SBP responses to the high sodium and potassium interventions (P=0.10 and 0.05). In addition, overall findings were similar when examining GRS as a continuous measure. Contrary to our initial hypothesis, we identified an inverse relationship between BP GRS and salt- and potassium-sensitivity of BP. These data may provide novel implications regarding the relationship between BP responses to dietary sodium and potassium and hypertension.